Chronic thromboembolic pulmonary hypertension (CTEPH): Updated Recommendations from the Cologne Consensus Conference 2018. (1st December 2018) - Wilkens, Heinrike; Konstantinides, Stavros; Lang, Irene M.; Bunck, Alexander C.; Gerges, Mario; Gerhardt, Felix; Grgic, Aleksandar; Grohé, Christian; Guth, Stefan; Held, Matthias; Hinrichs, Jan B.; Hoeper, Marius M.; et al.
Abstract: Chronic thromboembolic pulmonary hypertension (CTEPH) is a subgroup of pulmonary hypertension that differs from all other forms of PH in terms of its pathophysiology, patient characteristics and treatment. For implementation of the European Guidelines on Diagnosis and Treatment of Pulmonary Hypertension in Germany, the Cologne Consensus Conference 2016 was held and last updated in spring of 2018. One of the working groups was dedicated to CTEPH, practical and controversial issues were commented and updated. In every patient with suspected PH, CTEPH or chronic thromboembolic disease (CTED, i.e. symptomatic residual vasculopathy without pulmonary hypertension) should be excluded. Primary treatment is surgical pulmonary endarterectomy (PEA) in a multidisciplinary CTEPH centre. Inoperable patients or patients with persistent or recurrent CTEPH after PEA are candidates for targeted drug therapy. There is increasing experience with balloon pulmonary angioplasty (BPA) for inoperable patients; this option, like PEA, is reserved for specialised centres with expertise in this treatment method.